Urgent Need to Improve the Quality of Case Report in Traditional Chinese Medicine： Assessment on Reporting Quality of 3,417 Cases - 付姝菲 管伟 曾筱茜 张莉 郑颂华 宋丽 钟丽丹 林佳 王永炎 商洪才 卞兆祥 (Chinese journal of integrative medicine, 2016)
Objective： To survey the reporting quality of traditional Chinese medicine （TCM） case reports published in recent years and understand the common problems. The assessment results would lay the foundation for the development of recommendations for case report in Chinese medicine. Methods： This survey determined the reporting quality of cases with Chinese herbal decoction, Chinese proprietary medicine, acupuncture, moxibustion and other traditional therapies published in 20 core medical journals of China by searching the China Academic Journals Full-text Database from 2006 to 2010. Fifty survey items in 16 domains were used to determine the reporting quality. One point was assigned to each item （Yes=l point; No=0 point）, and total score was 50 points. The domain of treatment was assessed independently, ranging from 2 to 9 items for different TCM interventions. Results： The total of 1,658 case reports, covering 3,417 cases were included to analyze from 13 out of 20 core medical journals of China. There were 74.8% of them did not identify the nature of study in title, while 73.9% did not comprise an abstract. Incomplete reporting was found in discussions/ comment, and only 38.9% had made recommendations or take-away messages. Figures and tables were infrequently used. Three cases cited the full names of patients, but without declaring that any consent was obtained. Over 90% reported the symptoms and signs of TCM, and characteristics on tongue and pulse, but less than 50% did mention other medical history and diagnostic rationale. More than 90% treatments of the included cases were herbal decoction, with clear reporting on the ingredients and dosages. However, the reporting rate of the dosages of each ingredient was just 48.4%. Almost none reported the quality control of crude herbs, manufacturers and lot numbers of herbal proprietary medicine. Besides, advices and precautions on diet, emotions and living were rare to be illustrated. Conclusion： Systematic reporting recommendations are urged to develop for improving the contents and format of case reports in TCM.